Effect of Soil Nail on Stability of Slope - Ahmad Sayuthy, Afif Aiman; Felix Ling Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2024)
The behavior of the soil and the characteristic of the failure modes involved is important before develop any construction of retaining structures. All the information data collections are to ensure that no errors happen during construction and to provide and efficient economic solution. Every site will have the different condition and characteristic of soil because soil is unique material which form by continuous and complex process. The uses of soil nailing are chosen because it increases the structure stability and is critical in enabling the walls to take increased loads. It is used due its characteristic to withstand the shear strength and slope based on the soil condition. Soil is composing of granular aggregate particles which can be extracted by mechanical action (Craig, 1997). A case study at Putrajaya, Kuala Lumpur will be conducted for model verification. In this study, the analysis of soil nailing will be conducted in parametric study by using Finite Element software, PLAXIS LE to determine the effect of rainfall on the deformation of slope with the input of soil nail.